Circadian Gene Expression Rhythms During Critical Illness. Issue 12 (December 2020) - Maas, Matthew B.; Iwanaszko, Marta; Lizza, Bryan D.; Reid, Kathryn J.; Braun, Rosemary I.; Zee, Phyllis C.
Abstract : Objectives: Core clock genes regulate tissue-specific transcriptome oscillations that synchronize physiologic processes throughout the body, held in phase by the central circadian rhythm. The central circadian rhythm rapidly dampens with onset of critical illness, but the effect of critical illness on gene expression oscillations is unknown. The objective of this study was to characterize the rhythmicity and phase coherence of core clock genes and the broader transcriptome after onset of critical illness. Design: Cross-sectional study. Setting: ICUs and hospital clinical research unit. Patients: Critically ill patients within the first day of presenting from the community and healthy volunteers. Interventions: Usual care (critically ill patients) and modified constant routine (healthy volunteers). Measurements and Main Results: We studied 15 critically ill patients, including 10 with sepsis and five with intracerebral hemorrhage, and 11 healthy controls. The central circadian rhythm and rest-activity rhythms were profiled by continuous wrist actigraphy, and serum melatonin sampled every 2 hours along with whole blood for RNA isolation over 24 hours. The gene expression transcriptome was obtained by RNA sequencing. Core clock genes were analyzed for rhythmicity by cosinor fit. Significant circadian rhythmicity was identified in five of six core clock genes in healthy controls, but none in critically ill patients. TimeSignature, a validated algorithm based on 41 genes, was applied to assess overall transcriptome phase coherence. Median absolute error of TimeSignature was higher in individual critically ill patients than healthy patients (4.90 vs 1.48 hr) and was correlated with encephalopathy severity by Glasgow Coma Scale in critically ill patients (rho, –0.54; p = 0.036). Conclusions: Gene expression rhythms rapidly become abnormal during critical illness. The association between disrupted transcriptome rhythms and encephalopathy suggests a path for future work to elucidate the underlying pathophysiology.